1998
DOI: 10.1038/bjc.1998.61
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytotoxicity of [123I]IUdR, [125I]IUdR and [131I]IUdR to human glioma cells in monolayer or spheroid culture: effect of proliferative heterogeneity and radiation cross-fire

Abstract: Radioiodinated iododeoxyuridine (IUdR) is a novel, cycle-specific agent that has potential for the treatment of residual malignant glioma after surgery. As only cells in S-phase incorporate IUdR into DNA, a major limitation to this therapy is likely to be proliferative heterogeneity of the tumour cell population. Using a clonogenic end point, we have compared the toxicities of three radioiodoanalogues of IUdR--[123I]IUdR, [125I]IUdR and [131I]IUdR--to the human glioma cell line UVW, cultured as monolayers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…As expected, the cell kill increased with increasing proportion of NAT‐expressing cells. As was seen in previous studies, cytotoxicity was more pronounced in the three‐dimensional spheroids, probably as a result mainly of radiation cross‐fire which is more efficacious in three‐dimensions6, 7, 19, 20. In the present study, the response of TMS to [ 131 I]MIBG treatment was evaluated by clonogenic assay and spheroid growth delay.…”
Section: Discussionsupporting
confidence: 73%
“…As expected, the cell kill increased with increasing proportion of NAT‐expressing cells. As was seen in previous studies, cytotoxicity was more pronounced in the three‐dimensional spheroids, probably as a result mainly of radiation cross‐fire which is more efficacious in three‐dimensions6, 7, 19, 20. In the present study, the response of TMS to [ 131 I]MIBG treatment was evaluated by clonogenic assay and spheroid growth delay.…”
Section: Discussionsupporting
confidence: 73%
“…This type of collateral cell kill has previously been demonstrated using the tumor spheroid culture system. Cunningham et al [70] and Neshasteh-Riz et al [71] have shown that the effectiveness of cell kill by [ 131 I]-labelled compounds is significantly underestimated using monolayer cultures of target tumour cells whereas the impressive collateral damage inflicted by this means is amply demonstrated using threedimensional cellular aggregates.…”
Section: Mosaic Spheroid Model For the Assessment Of Targeted Radio-tmentioning
confidence: 98%
“…(2)). The increased effectiveness of radionuclide treatment of cellular aggregates is due to the enhanced efficiency of absorption of decay energy in three dimensional cultures [49,70,71]. If the administered radioisotope of iodine was 131 I (half-life = 8 days), the short residence time in NIS-expressing cells would diminish the radiation dose to tumours.…”
Section: Receptor Gene Expression To Facilitate Peptide Targetingmentioning
confidence: 98%
“…The increased effectiveness of radionuclide treatment of cellular aggregates is due to the enhanced efficiency of absorption of decay energy in three-dimensional cultures [34, 44]. This cross fire irradiation phenomenon (Figure 3) is an especially attractive feature of gene therapy schemes involving cellular concentration of radionuclides since gene transfer is notoriously inefficient, necessitating a mechanism which achieves bystander cell kill.…”
Section: Evaluation Of Radiological Bystander Effectsmentioning
confidence: 99%